2007
DOI: 10.1158/1541-7786.mcr-06-0258
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DEIN, a Novel Gene with High Expression Levels in Stage IVS Neuroblastoma

Abstract: Neuroblastoma at stage IVS, defined by dissemination to specific tissues and age <1 year at diagnosis, regularly follows spontaneous regression without cytotoxic treatment. To uncover the molecular characteristics of this subtype, Serial Analysis of Gene Expression (SAGE) profiles from stage IVS and fatal stage IV tumors were compared. A SAGE tag (GCAACTTAAC) was detected that was overrepresented in stage IVS disease and that had no reliable match in current National Center for Biotechnology Information databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 25 publications
4
19
0
Order By: Relevance
“…DEIN has been shown to be differentially expressed in neuroblastoma subtypes, with higher expression in tumors with good prognosis and spontaneous regression (children <1 year and in Stage IVS). No significant association between DEIN and MYCN amplification was reported (94). The expression of DEIN has been shown to be tightly linked to expression of the PHOX2B-downstream target HAND2 through a bidirectional promoter.…”
Section: N-myc Alters Expression Of Other Noncoding Rnasmentioning
confidence: 99%
“…DEIN has been shown to be differentially expressed in neuroblastoma subtypes, with higher expression in tumors with good prognosis and spontaneous regression (children <1 year and in Stage IVS). No significant association between DEIN and MYCN amplification was reported (94). The expression of DEIN has been shown to be tightly linked to expression of the PHOX2B-downstream target HAND2 through a bidirectional promoter.…”
Section: N-myc Alters Expression Of Other Noncoding Rnasmentioning
confidence: 99%
“…Therefore, the dysfunction of the enriched tumor suppressor genes probably drives the initiation and progression of breast cancer. Several cancer associated lncRNAs including the common ceRNA hubs like HAND2-AS1 (DEIN) [44, 45] and RP11-276H19.1 [46], as well as subtype-specific hubs like ADAMTS9-AS2, a luminal A specific hub lncRNA, acted as tumor suppressors and inhibited the migration of the glioma cells [47]. Similarly, functional analysis of the miRNA hubs by the TAM tool showed that the common and specific miRNA hubs play important roles in breast cancer subtypes (Supplementary Table 8) [48].…”
Section: Discussionmentioning
confidence: 99%
“…Significant methylation was found in the promoter region of LAMC3 in breast cancer (Kuznetsova et al 2007). HAND2-AS1, also known as DEIN, was first identified by Voth et al (2007) displaying high expression level in stage IVS neuroblastoma. Similarly, Lin and Chuang (2012) found repressed expression of LINC00261 in primary cultured invasive phenotype HCC cells compared Fig.…”
Section: Discussionmentioning
confidence: 99%